Hiding in the Shadows : The Growth of the Underground Economy - Schneider, Friedrich (Economic Issues; Economic Issues ;, 2003)
Examines the role of the shadow, or underground, economy. Looks at ways of measuring it, the relationship between the shadow economy and the main stream economy, why it has been growing in size, and its effects on overall economic growth. How can states limit the size of the shadow economy, and does it matter that it exists?